Bureaucracy Reform in Improving Integrated District Administrative Services - Bharoto, RM Haryo; Harsono, Yhonanda; Lestari, Aghnia Dian; Maharani, Shara (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2022)
Bureaucratic Reform of District Integrated Administrative Services (PATEN) The study at the Rajagaluh District Office, Majalengka Regency has the aim of explaining the bureaucratic reforms implemented by PATEN in improving service quality in Rajagaluh District and the supporting factors, obstacles to the successful implementation of PATEN in Rajagaluh District. The research method uses descriptive qualitative where the author uses information from the Rajagaluh District agencies and outside parties as a data balancer, namely the community. The results of this study indicate that the success of PATEN implementation in Rajagaluh District is seen in the PATEN implementation process through the behavior of PATEN employees, infrastructure, forms of commitment in implementing PATEN and service accountability. This makes Rajagaluh District strive to realize Bureaucratic Reform in its environment. The existence of PATEN not only aims to improve the quality of service in the District but also brings it closer to the community. Changes that occur through PATEN such as the provision of service facilities, a modern service system and the behavior of PATEN employees in accordance with service standards. Supporting factors in the success of PATEN are organizational capacity, coordination of interactions between actors involved and strategies for delivering information through a persuasive approach that lead to increased services such as training and improvement of infrastructure. In addition, this has a positive impact on the community so that people are satisfied with the existence of PATEN in Rajagaluh District. Despite the limited budget in increasing the capacity of human resources and infrastructure. The conclusion of the study is that in providing public services through PATEN it is related to PATEN officers so that there is a need for bureaucratic reform to achieve good governance. Therefore, the PATEN policy can produce institutions that are committed to advancing bureaucratic reform and paying attention to the needs of the community in public services.